Planetary health education in undergraduate medical education in Germany: results from structured interviews and an online survey within the national PlanetMedEd Project - Grieco, Fabio; Parisi, Sandra; Simmenroth, Anne; Eichinger, Michael; Zirkel, Janina; König, Sarah; Jünger, Jana; Geck, Eva; Schwienhorst-Stich, Eva-Maria (Frontiers in Medicine, 2025)
BackgroundIn light of the accumulating evidence, awareness and urgency to act upon the three planetary crises – climate change, biodiversity loss, and pollution – the concept of Planetary Health underscores their profound implications for health and promotes actionable solutions to advance both wellbeing and ecological sustainability. Despite (inter)national calls to integrate Planetary Health into health workers’ curricula, the current status of Planetary Health Education in undergraduate medical education in Germany is unclear. This study therefore aimed (a) to assess the current implementation of Planetary Health in undergraduate medical education in Germany and (b) to explore its characteristics as a foundation to develop evidence-informed recommendations for mainstreaming Planetary Health Education in medical schools in Germany.MethodsThe study comprised structured interviews followed by an online survey, both targeting all 39 medical schools in Germany. In 2021, structured interviews were conducted with students, educators and deanery staff at medical schools. In 2023, educators and deanery staff participated in an online survey based on the findings from the interviews.FindingsIn total, 80% of the 39 medical schools participated in the interviews, while 90% took part in the online survey. Based on integrated findings, 35 medical schools (90%) offered Planetary Health Education, with a median of two educational activities, including both stand-alone courses and lectures integrated into other courses. Despite an overall increase since winter semester 2021/2022, most educational activities were electives and not part of the mandatory curriculum. Innovative educational approaches and learning objectives differed significantly between mandatory and elective formats. In contrast to mandatory educational activities, student involvement was reported for the majority of electives and was significantly associated with transformative learning objectives.InterpretationDespite a steady rise in teaching activities, mandatory Planetary Health Education remains insufficiently integrated into undergraduate medical education in Germany. Key criteria defining high-quality Planetary Health Education, such as innovative educational approaches, practical skills, and transformative learning, were primarily reflected in electives, that reach only a minority of students. To adequately equip the future healthcare workforce, the current barriers to successfully integrating Planetary Health into medical education must be systematically addressed and overcome.